Building Customer Loyalty through Relationship Quality - Andhika Hendrianto; Mas Wahyu Wibowo (Journal of Sustainable Economic and Business, 2026)
Objectives: This study aims to examine the effects of relationship quality dimensions, namely customer satisfaction, trust, and commitment, on customer loyalty in a Business-to-Business (B2B) context within the manufacturing industry at PT Indonesia Steel Tube Works (ISTW).Methodology: This research employs a quantitative approach using a survey method, with data collected from 119 B2B customers of PT ISTW who are directly involved in purchasing decision-making processes.Finding: The results show that customer satisfaction and trust do not have a significant direct effect on customer loyalty, indicating that in mature B2B relationships these variables primarily function as basic relational prerequisites rather than key drivers of loyalty. Conversely, commitment has a positive and significant effect on customer loyalty, highlighting the importance of relational attachment and a long-term orientation in sustaining B2B partnerships.Conclusion: This study concludes that commitment represents the primary determinant of customer loyalty in B2B manufacturing relationships.